The electrocardiogram is a more sensitive indicator than echocardiography of hypertrophic cardiomyopathy in families with a mutation in the MYH7 gene. Issue 2 (August 1994) - al-Mahdawi, S; Chamberlain, S; Chojnowska, L; Michalak, E; Nihoyannopoulos, P; Ryan, M; Kusnierczyk, B; French, J A; Gilligan, D M; Cleland, J
Abstract : BACKGROUND–Mutations in the cardiac beta myosin heavy chain gene causing hypertrophic cardiomyopathy have been identified, and to assist both diagnosis and prediction of outcome attempts have been made to correlate phenotype and genotype. Two new mutations in codon 403 of the gene in three unrelated families are described and attention drawn to variable or even absent phenotypic expression in different family members. METHODS AND RESULTS–The polymerase chain reaction and heteroduplex analysis on Mutation Detection Enhancement gels were used to search for mutations in the globular head of the beta myosin heavy chain gene in families with hypertrophic cardiomyopathy. Two mutations were found in exon 13 (codon 403) of the gene. In two unrelated Polish families the mutation resulted in the conversion of arginine to tryptophan (CGG–>TGG). A second mutation, found in a British family, converted the same arginine to leucine (CGG–>CTG). These mutations were detected in family members who had electrocardiographic and echocardiographic features typical of hypertrophic cardiomyopathy; however, they were also detected in 7 other adult relatives with an abnormal electrocardiogram but a normal echocardiogram. Two unrelated adult relatives had completely normal clinical findings but carried the gene mutation. CONCLUSIONS–Identification of a specific mutation gives no guide to the clinical phenotype. There is considerable variability in the phenotypic expression of hypertrophic cardiomyopathy. Mutations were detected in adults previously regarded as normal or in whom the diagnosis was questionable. The fact that the clinical significance of the mutation in these people is still unknown emphasises the dilemma facing screening programmes. Isolated, unexplained electrocardiographic abnormalities in first degree relatives in a family with a definitive diagnosis of hypertrophic cardiomyopathy should be regarded as evidence of a carrier state.